Let's solve each of the problems step by step.
-
Multiply \( \sqrt{93} \cdot \sqrt{67} \)
\[ \sqrt{93} \cdot \sqrt{67} = \sqrt{93 \cdot 67} \]
Now calculate \( 93 \cdot 67 \):
\[ 93 \cdot 67 = 6231 \]
So the exact answer is:
\[ \sqrt{6231} \]
-
Multiply \( \sqrt{11} \cdot \sqrt{67} \)
\[ \sqrt{11} \cdot \sqrt{67} = \sqrt{11 \cdot 67} \]
Now calculate \( 11 \cdot 67 \):
\[ 11 \cdot 67 = 737 \]
So the exact answer is:
\[ \sqrt{737} \]
-
Divide \( \frac{2\sqrt{65}}{\sqrt{5}} \)
You can simplify by multiplying numerator and denominator by \( \sqrt{5} \):
\[ \frac{2\sqrt{65}}{\sqrt{5}} \cdot \frac{\sqrt{5}}{\sqrt{5}} = \frac{2\sqrt{65 \cdot 5}}{5} = \frac{2\sqrt{325}}{5} \]
Since \( 325 = 25 \cdot 13 \):
\[ = \frac{2 \cdot \sqrt{25 \cdot 13}}{5} = \frac{2 \cdot 5 \cdot \sqrt{13}}{5} = 2\sqrt{13} \]
So the exact answer is:
\[ 2\sqrt{13} \]
-
Divide \( \frac{9\sqrt{33}}{27\sqrt{11}} \)
This can be simplified by dividing both the numerator and the denominator:
\[ \frac{9}{27} = \frac{1}{3} \]
The square root part can also be simplified:
\[ \frac{\sqrt{33}}{\sqrt{11}} = \sqrt{\frac{33}{11}} = \sqrt{3} \]
Thus the answer becomes:
\[ \frac{1}{3}\sqrt{3} \]
So, the exact answer is:
\[ \frac{\sqrt{3}}{3} \]
-
Simplify \( 7\sqrt{99} \)
First factor \( 99 \):
\[ 99 = 9 \cdot 11 = 3^2 \cdot 11 \]
Now we can simplify:
\[ 7\sqrt{99} = 7\sqrt{9 \cdot 11} = 7\sqrt{9} \cdot \sqrt{11} = 7 \cdot 3 \sqrt{11} = 21\sqrt{11} \]
So the exact answer is:
\[ 21\sqrt{11} \]
In summary, the answers are:
- \( \sqrt{6231} \)
- \( \sqrt{737} \)
- \( 2\sqrt{13} \)
- \( \frac{\sqrt{3}}{3} \)
- \( 21\sqrt{11} \)